Adsorptive removal of Ni and Cd from wastewater using a green longan hull adsorbent - Xingmei Guo; Sihan Tang; Yan Song; Junmin Nan (Adsorption Science & Technology)
The adsorptive removal of Ni 2+ and Cd 2+ at concentrations of approximately 50 mg L −1 in wastewater is investigated using an agricultural adsorbent, longan hull, and the adsorptive mechanism is characterized. The maximum adsorption capacity of approximately 4.19 mg g −1 Cd 2+ was obtained under the optimized conditions of room temperature, pH 5.0, and a solid-to-liquid ratio of 1:30 in approximately 15 min. For Ni 2+ , the maximum adsorption capacity of approximately 3.96 mg g −1 was obtained at pH 4.7 in approximately 20 min. The adsorption kinetics for both metal ions on the longan hull can be described by a pseudo second-order rate model and are well fitted to the Langmuir adsorption isotherm. The adsorption mechanism of the longan hull to Ni 2+ and Cd 2+ ions is shown to be a monolayer adsorption of metal ions onto the absorbent surface. Thereinto, the longan hull adsorbent contains N–H, C–H, C=O, and C=C functional groups that can form ligands when loaded with Ni 2+ and Cd 2+ , which reduces the fluorescence of the dried longan hull material.